Artistic Functions of Inversion in Contemporary Uzbek Poems - Karimova Shakhnozakhon Karimovna (Researchparks Publishing, 2022)
The article investigates inversion as a reducing figures in Uzbek contemporary poems. Furthermore, the analysis of poems are shown that inversion is carried out with an emotional tonality in poems and it serves to create an artistic content in verse poems.